2018
DOI: 10.1680/jmacr.17.00016
|View full text |Cite
|
Sign up to set email alerts
|

Towards innovative FRP fabric reinforcement in concrete beams: concrete–CFRP bond

Abstract: The paper reports results of an experimental investigation into load response and failure behaviour of rectangular prismatic concrete beams reinforced with a combined flexural and shear reinforcement system made from carbon fibre reinforced polymer (CFRP) fabric. It is shown that CFRP U-channels with aggregate coating and an anchorage system consisting of a lipped channel section with intermittent closed loops were found to provide improved composite action between the CFRP reinforcement and concrete. These CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Over the last few decades, the use of FRP as reinforcement in concrete members has gained interest among the researchers and designers owing to the corrosion resistance, high strength and low-weight characteristics of the materials. (Achintha et al 2018;Achintha M 2009;Lou et al 2016Lou et al , 2017ab;Lou and Karavasilis 2018;Sun et al 2017aSun et al , 2018Sun 2018;Sun et al 2016Sun et al , 2017bSun and Ghannoum 2015). Despite FRPs being more expensive than steel on a unit weight basis, it is anticipated that the innovative use of the material together with its long-term benefits such as low maintenance and high durability may enable FRP reinforcement systems to be a viable alternative to steel reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, the use of FRP as reinforcement in concrete members has gained interest among the researchers and designers owing to the corrosion resistance, high strength and low-weight characteristics of the materials. (Achintha et al 2018;Achintha M 2009;Lou et al 2016Lou et al , 2017ab;Lou and Karavasilis 2018;Sun et al 2017aSun et al , 2018Sun 2018;Sun et al 2016Sun et al , 2017bSun and Ghannoum 2015). Despite FRPs being more expensive than steel on a unit weight basis, it is anticipated that the innovative use of the material together with its long-term benefits such as low maintenance and high durability may enable FRP reinforcement systems to be a viable alternative to steel reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimension (3D) FRP fabric reinforcements have been developed to provide a combined shear and 37 flexural reinforcement for concrete structures [16]. It is found that this 3D reinforcement can greatly 38 improve FRP-concrete bond allowing both adequate strength and desired ductility to be effectively 39 developed [16].…”
mentioning
confidence: 99%
“…Three-dimension (3D) FRP fabric reinforcements have been developed to provide a combined shear and 37 flexural reinforcement for concrete structures [16]. It is found that this 3D reinforcement can greatly 38 improve FRP-concrete bond allowing both adequate strength and desired ductility to be effectively 39 developed [16]. Further development of the 3D reinforcement is expected to aid in achieving structurally 40 optimized (non-prismatic) concrete members consuming significantly less concrete materials [17], and 41 be used for stay-in-place formwork therefore significantly reducing the required construction effort [18].…”
mentioning
confidence: 99%
See 2 more Smart Citations